Manipulation Of Ideological And Culture-Specific Items In The Audiovisual Translation From French Into Arabic Of Voiced-Over Documentaries - Chabbak, Salma (2018)
While audiovisual translation (AVT) continues to influence the audience‟s culture and identity in a largely globalized world, there is a noticeable inequality between this growing influence and the research carried out in the field in the Arab World. The engaged efforts made by some researchers fall short of covering the multilayered practices and phenomena related to AVT in the Arab World, despite the variety of the translated genres and the modes of transfer in use. As a matter of fact, the voiced-over documentary is one of the most abundantly translated genres in the Arab World and carries lots of cultural and ideological elements which are in many cases rendered by manipulation. However, voiced-over documentaries have hardly received any focused attention from researchers in the Arab World. This study attempts to scrutinize the process of translation of voiced-over documentaries in the Arab World, from French into Arabic in the present case study, by sub-categorizing ideological and culture-specific items subject to manipulation, identifying the techniques utilized in their translation and exploring the extra-linguistic factors that prompt translation agents to opt for manipulative translation. The investigation is based on a corpus of 94 episodes taken from a culturally-oriented series entitled 360° Geo Reports, produced by the French German network ARTE in French, and translated and aired by Al Jazeera Documentary Channel for Arab audiences. The results yielded 318 cases of manipulation in 8 sub-categories of ideological and culture-specific items, the use of 10 different oblique procedures in the process of manipulative translation. The study also revealed that manipulation is dictated by the editorial line of the broadcasting channel, in addition to the religious, geopolitical and socio-cultural peculiarities of the target culture. Other extra-linguistic factors related to technical constraints were also noted.